The Implementation Of Gold Dinar: Is It The End Of Speculative Measures? - Abu Bakar Mohd Yusuf; Nurhayati Mat Husin; Nuradli Ridzwan Shah Mohd Dali (Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2024)
Non-Indexed Publication